2019
DOI: 10.1093/ccc/tcz039
|View full text |Cite
|
Sign up to set email alerts
|

Bugs: Rethinking the History of Computing

Abstract: This paper argues that scholars of computing, networks, and infrastructures must reckon with the inseparability of “viral” discourses in the 1990s. This co-assembled history documents the reliance on viral analogies and explanations honed in the HIV/AIDS crisis and its massive loss of life, widespread institutional neglect, and comprehensive technological failures. As the 1990s marked a period of intense domestication of computing technologies in the global North, we document how public figures, computer exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The word infodemic is not the first word that has been borrowed from health as researchers and information managers have talked about how social media companies should "flatten the curve" of misinformation. For instance, McKinney and Mulvin (2019) have shown that computer viruses are terminology that emerged in the 1990s from an analogy to the HIV/AIDS pandemic. WHO (2022) conceptualized infodemic as "too much information including false or misleading information in digital and physical environments during a disease outbreak".…”
Section: Concept Of Infodemic Towards Covid-19 Vaccinationmentioning
confidence: 99%
“…The word infodemic is not the first word that has been borrowed from health as researchers and information managers have talked about how social media companies should "flatten the curve" of misinformation. For instance, McKinney and Mulvin (2019) have shown that computer viruses are terminology that emerged in the 1990s from an analogy to the HIV/AIDS pandemic. WHO (2022) conceptualized infodemic as "too much information including false or misleading information in digital and physical environments during a disease outbreak".…”
Section: Concept Of Infodemic Towards Covid-19 Vaccinationmentioning
confidence: 99%
“…For those of us who remember it, that was a year which was predicted to lead to a global computer problem: the Y2K bug. The Y2K bug referred to potential computer malfunction because of how calendar dates were formatted and stored (in six digits instead of eight) (Aspinwall et al 2005 ; McKinney and Mulvin 2019 ). As the impending 2000 calendar year approached closer, there was widespread speculation of Y2K’s impact on all related technology.…”
mentioning
confidence: 99%